The effect of work stress towards work-life balance among employees at Jabatan Kehakiman Syariah Selangor (JAKESS) / Norsyahirah Mat Sani - Mat Sani, Norsyahirah (Faculty of Business and Management, 2019)
Work-life balance is a term used for the idea that individual need time for both work and other aspects of life, whether those are family-related or personal interests. If there any imbalance in life of individual, it will results the employee start to feel stress and fatigue, loss of control and even strained relationships. Thus, achieving a work-life balance is the new ideal for employees and the need of balance is essential because the previous studies have reported that work-life balance bring more benefits to the organizations who applied it in their company‘s policy. Furthermore, this study focuses on how the effect of work stress towards the work-life balance among the employees at Jabatan Kehakiman Syariah Selangor (JAKESS). There are 304 questionnaire were distribute to the employees by using the convenience sampling method and the response rate are gathered from this study at 70% of population. In this study, the data analysis shows that, workload have a negative and significant relationship towards work-life balance. Meanwhile, interpersonal relationship has positive and significant relationship towards work-life balance. However, the finding shows that role conflict has no significant relationship towards work-life balance at Jabatan Kehakiman Syariah Selangor (JAKESS). Moreover, interpersonal relationship has become the strongest relationship towards work-life balance among employees at Jabatan Kehakiman Syariah Selangor (JAKESS).